WHITE PAPER ON FORWARD PHYSICS, BFKL, SATURATION PHYSICS AND DIFFRACTION - Hentschinski, Martin; Royon, Christophe; Peredo, Marco Alcazar; Baldenegro, Cristian; Bellora, Andrea; Boussarie, Renaud; Celiberto, Francesco Giovanni; Cerci, Salim; Chachamis, Grigorios; Contreras, J. G.; Fichetl, Sylvain [UNESP]; Fucilla, Michael; et al. (Jagiellonian Univ Press, 2023)
The goal of this white paper is to give a comprehensive overview of the rich field of forward physics. We discuss the occurrences of BFKL re-summation effects in special final states, such as Mueller-Navelet jets, jet-gap-jets, and heavy quarkonium production. It further addresses TMD factorization at low x and the manifestation of a semi-hard saturation scale in (generalized) TMD PDFs. More theoretical aspects of low -x physics, probes of the quark-gluon plasma, as well as the possibility to use photon- hadron collisions at the LHC to constrain hadronic structure at low x, and the resulting complementarity between LHC and the EIC are also presented. We also briefly discuss diffraction at colliders as well as the possibility to explore further the electroweak theory in central exclusive events using the LHC as a photon-photon collider.